2005
DOI: 10.1007/s10653-005-6982-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Iodine Deficiency and Goitre Incidence in Parts of Yewa Area of Ogun State, Southwestern Nigeria

Abstract: This study was carried out to determine the occurrence, prevalence and contributing factors to the incidence of goitre in Yewa north local government area of Ogun state, southwestern Nigeria. To achieve these objectives, soil, water, and cassava tubers were collected from four villages -- Igbogila, Egua, Sawonjo and Imoto and from Lagos (about 250 m to the ocean) as a reference location, in order to determine their iodine concentrations. The results of the analyses indicated a soil mean iodine range of 2.1-5.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…When water and soil samples were collected from the same location, soil and water iodine values exhibited a positive correlation of 0.865 (P < 0.01). Gbadebo and Oyesanya (2005) reported a lower correlation of 0.756 (P < 0.05) between the water and soil iodine values in Nigeria. Fuge (1989) found no correlation between water and soil values in the UK and suggested that water-iodine data could not be reliable in identifying goitrous areas.…”
Section: Resultsmentioning
confidence: 85%
“…When water and soil samples were collected from the same location, soil and water iodine values exhibited a positive correlation of 0.865 (P < 0.01). Gbadebo and Oyesanya (2005) reported a lower correlation of 0.756 (P < 0.05) between the water and soil iodine values in Nigeria. Fuge (1989) found no correlation between water and soil values in the UK and suggested that water-iodine data could not be reliable in identifying goitrous areas.…”
Section: Resultsmentioning
confidence: 85%
“…Generally, low iodine contents have been found, i.e., in North America [14], South America [31], Africa [32], Europe [9,18,33], Asia [34] and Australia [15]. However, markedly higher iodine contents of drinking water were found in a few locations [11,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…1) which has already been delineated by Gbadebo and Oyesanya (2005) as a goitre prone area. The locations of the study were the communities of Igbogila, Egua, Sawonjo and Imoto, while the University of Agriculture, Abeokuta (UNAAB) community was used as control study area.…”
Section: The Study Areamentioning
confidence: 99%
“…The locations of the study were the communities of Igbogila, Egua, Sawonjo and Imoto, while the University of Agriculture, Abeokuta (UNAAB) community was used as control study area. Details about the climatic conditions, geology and soils of the study areas can be found in the work of Gbadebo and Oyesanya (2005).…”
Section: The Study Areamentioning
confidence: 99%